Dissecting and tracing the gut microbiota of infants with botulism: a cross sectional and longitudinal study - Wang, Dai; Li, Kexin; Wang, Lijuan; Teng, Zhongqiu; Luo, Xia; Sun, Hui; Huang, Ying; Hu, Songnian; Xu, Xuefang; He, Zilong (Frontiers in Microbiology, 2024)
Background. Infant botulism is caused by botulinum neurotoxin (BoNT), which is mainly produced by Clostridium botulinum. However, there is a lack of longitudinal cohort studies on infant botulism. Herein, we have constructed a cross-sectional and longitudinal cohort of infants infected with C. botulinum. Our goal was to reveal the differences in the intestinal microbiota of botulisminfected and healthy infants as well as the dynamic changes over time through multi-omics analysis.Methods. We performed 16S rRNA sequencing of 20 infants' stools over a period of 3 months and conducted whole genome sequencing of isolated C. botulinum strains from these laboratoryconfirmed cases of infant botulism. Through bioinformatics analysis, we focused on the changes in the infants' intestinal microbiota as well as function over time series.Results. We found that Enterococcus was significantly enriched in the infected group and declined over time, whereas Bifidobacterium was significantly enriched in the healthy group and gradually increased over time. 18/20 isolates carried the type B 2 botulinum toxin gene with identical sequences. in silico Multilocus sequence typing found that 20 C. botulinum isolates from the patients were typed into ST31 and ST32.Conclusions. Differences in intestinal microbiota and functions in infants were found with botulism through cross-sectional and longitudinal studies and Bifidobacterium may play a role in the recovery of infected infants.